Visual analysis of the research frontiers, hotspots and trends of exercise therapy intervention in tumor-related sleep-wake disorders - Han, Jilei; Zhang, Jiachen; Zhang, Litao; Guo, Juan; Peng, Xitao; Ying, Chenlin; Li, Zhiqing; Li, Mu; Chang, Lihua; Zhang, Yani (Frontiers in Oncology, 2024)
Objective To systematically understand the research frontiers, hotspots and development trends of exercise therapy in the intervention of tumor-related sleep-wake disorders, and to provide scientific basis for follow-up research. Methods Downloaded the original research papers on February 26, 2024, from the Web of Science core collection database, on tumor-associated sleep-wake disorders. The data that met the inclusion criteria were imported into the Bibliometric Analysis Platform (http://biblimetric.com), CiteSpace 6.3.R1 and VOSviwer1.6.20 software for visual analysis, and imported into Excel2021. Scientometric analysis was performed with Oringin2021 and PyCharm Community Edition 2022.1.3. Results A total of 512 original research papers on tumor-related sleep-wake disorders were obtained. The most influential countries in the subject area are the United States, Spain and German, the institutions are the University of California System, Sun Yat Sen University and Northwestern University, et al., the authors are Berger AM, Aaronson NK, Bower JE, et al., and the journals are Cancer, Brit J Cancer and Cancer Nurs. The co-cited references suggest that the current research frontier in the field mainly involves the level, place and program of exercise therapy, including the relationship between physical activity, sedentary behavior and cancer prevention and control. The results of co-occurrence keyword network analysis showed that quality of life, physical activity, breast cancer, exercise, fatigue, and survivors may be the research hotspots in this field, with breast cancer, health, aerobic exercise, adults, and chemotherapy being the most popular. Conclusions The number of papers published and the research enthusiasm in this field show a steady upward trend. However, there is a lack of influential institutions and scholars, and there is relatively little research collaboration across countries/regions/institutions. The scientific research influence of institutions and scholars in most European and American countries/regions is significantly ahead of that of institutions and scholars in Asian and African countries/regions. But Sun Yat Sen University in China is a relatively active and influential scientific research institution in recent years, which is worthy of attention. In addition, the research frontier of this discipline is the level, place and program of exercise therapy auxiliary intervention, and the research hotspots involve breast cancer, health, aerobic exercise, adults, chemotherapy, et al. Their clinical efficacy needs to be further demonstrated in multi-center, large-sample and high-quality prospective studies.